Whatever happened to the Washington reporters 1978-2012 - Hess, Stephen (Hess, Stephen. Newswork, 2012)
"Follows up on 450 Washington journalists first interviewed in 1978, analyzing career patterns and challenges faced by generation, gender, minority status, news medium, and employer. Explores whether subjects rose within their organization, moved from reporter to editor or from one medium to another, or left journalism and if so, why and for what kind of career"--